Financial Strategies for the Manager - Priester, Charles. (Tsinghua University Texts,, 2010)
Part of Tsinghua University Texts, Financial Strategies for the Manager includes a range of financial management issues such as financial statement analysis, a systematic approach to financial performance appraisal, liquidity management and sales growth, working capital management, budgeting, foreign exchange and interest rate risk management, and a most useful tool not normally understood – EVA. The book is written in a concise and accessible style, minimizing the use of the technical jargon and complicated mathematical formulae. Included exercises enhance student learning and examples bolster ability to understand and use concepts in day-to-day situations. The material was originally developed for a large corporate client in the telecommunications business to assist non-financial managers in understanding financial theories in a practical way. It was expanded and revised into a text for a post-graduate course of the Asia/Pacific Management Co-operative Program, Capilano University, BC, Canada. Charles Priester is a professor at Capilano University of Canada; Jincheng Wang is a professor at the International Business School of Tianjin Foreign Studies University of China.